A CLD-based tourist simulation system - Pornphol, Putsadee; Chittayasothorn, Suphamit (My University, 2014)
At present, the application of information systems in general and simulation systems in particular becomes apparent in many domains; both in business and government sectors. Accurate and timely information together with prediction results from decision support systems such as simulation systems help modern organizations advance ahead of the competition. Of course, the output of a simulation system is more accurate when the input is from reliable sources and high in quality. This paper presents the gross architecture of a tourist simulation system and the implementation details of its major subsystems. Causal Loop Diagrams (CLDs), conceptual schema, and temporal database play important roles in this research work.
Keywords: Casual Loop Diagrams; Decision Support System; Simulation; System Dynamic; Tourist Destination Assessment (TDAS); Tourist Simulation System (TSS)